Quantifying episodic erosion and transient storage on the western margin of the Tibetan Plateau, upper Indus River. Issue 1 (16th November 2017) - Jonell, Tara N.; Owen, Lewis A.; Carter, Andrew; Schwenniger, Jean-Luc; Clift, Peter D.
Abstract: Transient storage and erosion of valley fills, or sediment buffering, is a fundamental but poorly quantified process that may significantly bias fluvial sediment budgets and marine archives used for paleoclimatic and tectonic reconstructions. Prolific sediment buffering is now recognized to occur within the mountainous upper Indus River headwaters and is quantified here for the first time using optically stimulated luminescence dating, petrography, detrital zircon U-Pb geochronology, and morphometric analysis to define the timing, provenance, and volumes of prominent valley fills. This study finds that climatically modulated sediment buffering occurs over 10 3 –10 4 yr time scales and results in biases in sediment compositions and volumes. Increased sediment storage coincides with strong phases of summer monsoon and winter westerlies precipitation over the late Pleistocene (32–25 ka) and mid-Holocene (~8–6 ka), followed by incision and erosion with monsoon weakening. Glacial erosion and periglacial frost-cracking drive sediment production, and monsoonal precipitation mediates sediment evacuation, in contrast to the arid Transhimalaya and monsoonal frontal Himalaya. Plateau interior basins, although volumetrically large, lack transport capacity and are consequently isolated from the modern Indus River drainage. Marginal plateau catchments that both efficiently produce and evacuate sediment may regulate the overall compositions and volumes of exported sediment from the Himalayan rain shadow.